Iraq's quest for a social contract: An approach to promoting social cohesion and state resilience - Wolfgang Mühlberger (German Institute of Development and Sustainability (IDOS), 2023)
This study sets out to examine state-society relations in Iraq through the conceptual lens of the social contract and also provides a starting point for deriving potential areas of activity for external actors, such as German development cooperation (DC) and technical cooperation (TC). These players could provide support for the re-negotiation of this fraught mesh of relationships. This analysis is founded on a concept of the social contract in which the relationship between the government and those it governs is viewed primarily as a process of negotiation and can be operationalised, for instance, on the basis of the three Ps (participation, provision and protection). As such, the concept is informed both by contemporary approaches and by traditional reflections of French and Anglo-Saxon thinkers, who focus on the restriction of individual freedoms in return for the provision of legal certainty by the state. This study is divided into three sections. The first section explores weak statehood and the breakdown of society in the heuristic context of the social contract. The role of external actors in Iraq's post-2003 development is then examined in the next section, which takes a closer look at the political system of proportional representation and its socio-political implications. Finally, the third section synthesises the first two by considering how external actors from the development cooperation sector might contribute to the peaceful negotiation of Iraq's dysfunctional social contract. These reflections are made against the systemic backdrop of a rentier state with a hybrid form of governance and take account of the extremely fragile government-society relationship on the one hand, and external interventions, which have largely failed to date, on the other. In this context, the shortcomings of the largely dysfunctional Iraqi social contract become apparent and at the same time provide starting points for its improvement and renegotiation.
Keywords: 330; development cooperation (DC); external actors; financial cooperation (FC); fragile statehood; hybrid governance; post-conflict; social contract; social division; technical cooperation (TC)